A multistrain probiotic improves handgrip strength and functional capacity in patients with COPD: A randomized controlled trial. (September 2022) - Karim, Asima; Muhammad, Tahir; Shahid Iqbal, M.; Qaisar, Rizwan
Highlights: COPD patients present with muscle weakness and functional decline. Probiotics improve muscle strength and functional capacity in COPD patients. Probiotics repair neuromuscular junction and intestinal permeability in COPD. Probiotics may help boost functional dependency in elderly COPD patients. Abstract: Purpose: The age-related muscle loss, termed sarcopenia and functional dependency, are common findings in patients with chronic obstructive pulmonary disease (COPD). However, an effective bedside treatment remains elusive. Objective: To assess the effects of probiotics on sarcopenia and physical capacity in COPD patients. Methods: Randomized, double-blind, computer-controlled, multicenter trial in two tertiary-care hospitals for 16 weeks. A central computer system randomly allocated male, 63—73 years old COPD patients into placebo (n=53) and probiotic (n=51) groups. The intervention was Vivomix 112 billion*, one capsule a day for 16 weeks. The main outcomes measured were sarcopenia phenotype, short physical performance battery (SPPB), plasma markers of intestinal permeability (zonulin and claudin-3) and neuromuscular junction degradation (CAF22), body composition, and handgrip strength (HGS) before and following the probiotics treatment. Findings: 4 patients discontinued intervention due to poor compliance and 100 patients, including placebo (n=53) and probiotic (n=47) groups were analyzed. Probiotics reduced plasma zonulin, claudin-3, and CAF22, along with an improvement in HGS, gait speed, and SPPB scores (all p<0.05). Probiotic treatment also reduced the plasma c-reactive proteins and 8-isoprostane levels, the markers of systemic inflammation and oxidative stress (p<0.05). Correlation analysis revealed varying degrees of association of plasma biomarkers with sarcopenia indexes. Despite a statistical trend, we did not find a reduction in sarcopenia prevalence in the probiotic group. Conclusion: Taken together, the multistrain probiotic improves muscle strength and functional performance in COPD patients by reducing intestinal permeability and stabilizing neuromuscular junction. Trial registration: GMC clinical trial unit, GMC-CREC-00263